Muscular strength, balance, and functionality in post-COVID-19 patients: An observational case-control protocol: Muscle strength and balance in severe and critical post-covid-19 patients - Oliveira Gomes, Nadia; da Silva Junior, Jose Carlos; dos Santos Mendes, Felipe Augusto; Coutinho, Jean Carlos; Z Maldaner, Vinicius; da Silva Almeida, Isabella; Quagliotti Durigan, João Luiz; França Bernardelli Cipriano, Graziella; Cipriano Jr, Gerson (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Persistent and systemic impairments have been reported in individuals recovering from COVID-19, including balance and muscle strength dysfunctions. However, the implications for static and dynamic Balance and their potential associations with muscle strength and functional assessments in patients with severe disease during the acute phase remain poorly understood in the existing scientific literature. Objectives: This study evaluates static and dynamic balance, lower limb muscle strength, and physical capacity in post COVID volunteers who experienced severe and critical forms of the disease. Additionally, it seeks to identify potential correlations between functional outcomes and demographic characteristics. Methods: This observational case-control study will enroll individuals who had experienced severe and critical forms of COVID-19 during the acute phase of the illness. Static Balance will be assessed using a Portable Baropodometry and Stabilometry platform, while dynamic Balance will be evaluated through the MiniBest Test. Muscle strength will be measured by Isometric Quadriceps Muscle Strength during contraction of knee extension, flexion, and physical capacity utilizing the 1-minute Sit-to-Stand Test (1MST). Hypothesis: We hypothesize that Long COVID volunteers who endured severe and critical forms of the disease during the acute phase will exhibit: 1)Impaired static and dynamic Balance compared to a control group of individuals without a history of COVID-19, as evidenced by significantly different scores on Baropodometry and Stabilometry assessments, as well as the MiniBest Test. 2)Reduced lower limb muscle strength compared to the control group. 3) Decreased physical capacity as assessed by the 1-minute Sit-to-Stand Test (1MST) when compared to individuals without a history of COVID-19. 4) Possible associations between demographic characteristics (age, gender, and physical activity level) and the observed functional outcomes. We anticipate that these findings will contribute to a better understanding of the long-term effects of severe and critical COVID-19 on Balance, muscle strength, and physical capacity.